Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Du, Jiayu; Zhang, Xuliang; Zhang, Jian; Huo, Siming; Li, Bo; Wang, Qi; Song, Miao; Shao, Bing; Li, Yanfei (Food and chemical toxicology, 2023)
Aluminum (Al) is a common environmental pollutant that can induce kidney damage. However, the mechanism is not clear. In the present study, to explored the exact mechanism of AlCl3-induced nephrotoxicity, C57BL/6 N male mice and HK-2 cells were used as experimental subjects. Our results showed that Al induced reactive oxygen species (ROS) overproduction, c-Jun N-terminal kinase (JNK) signaling activation, RIPK3-dependent necroptosis, NLRP3 inflammasome activation, and kidney damage. In addition, inhibiting JNK signaling could downregulate the protein expressions of necroptosis and NLRP3 inflammasome, thereby alleviating kidney damage. Meanwhile, clearing ROS effectively inhibited JNK signaling activation, which in turn inhibited necroptosis and NLRP3 inflammasome activation, ultimately alleviating kidney damage. In conclusion, these findings suggest that necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage. [Display omitted]